Once was Willem - Carey, M. R., 1959- (Orbit Books, 2025)
"Eleven hundred and some years after the death of Christ, in the kingdom that had but recently begun to call itself England, I, Once Was Willem, rose from the dead to defeat a great evil facing the humble village of Cosham. The words enclosed herein are true. I speak of monsters and magic, battle and bloodletting, and the crimes of desperate men. I speak also of secret things, of that which lies beneath us and that which impends above. By the time you come to the end of this account you will know the truth of your own life and death, the path laid out for your immortal soul, your origin and your inevitable end. You will not thank me."--Amazon.